Logics of stratified identity management in world politics. Issue 2 (11th January 2019) - Ward, Steven
Abstract: The importance of concerns about status in world politics has rarely been as evident as it is today. Yet our understanding of how status dynamics influence politics and foreign policy remains limited. Dominant approaches draw on insights from social psychology about individual attitudes and behavior, but scale these up to build accounts of states as unitary or anthropomorphic actors. This results in serious theoretical problems and analytical blind spots. In this article, I offer a new framework – still rooted in social psychological insights about intergroup status dynamics – that addresses these problems. I recast the fundamental question from one about how states react to status dissatisfaction to one about how individuals – with different psychological profiles, different interests, and different positions within the national community – react to anxiety about the status of the state with they identify. I develop four broad logics that inform responses to national status dissatisfaction: identification change, emulation, transformation, and rejection. These logics subsume familiar arguments about how states seek status, but they also accommodate additional variation and explanatory possibilities. They thus constitute a more flexible framework that is better suited than existing alternatives to understand the full variety of ways in which status dynamics may influence world politics.